2019
DOI: 10.1103/physrevresearch.1.012009
|View full text |Cite
|
Sign up to set email alerts
|

Stability of quantum degenerate Fermi gases of tilted polar molecules

Abstract: A recent experimental realization of quantum degenerate gas of 40 K 87 Rb molecules opens up prospects of exploring strong dipolar Fermi gases and many-body phenomena arising in that regime. Here we derive a mean-field variational approach based on the Wigner function for the description of ground-state properties of such systems. We show that the stability of dipolar fermions in a general harmonic trap is universal as it only depends on the trap aspect ratios and the dipoles' orientation. We calculate the spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…This is three times higher than what was reached in degenerate Fermi gases of magnetic atoms [42]. In the near future, intriguing dipolar many-body phenomena such as modifications of collective excitation modes [43], distortion [42] or the collapse [44] of the Fermi sea should be observable in suitable trap geometries and with improved detection of the cloud expansion.…”
Section: Discussionmentioning
confidence: 79%
“…This is three times higher than what was reached in degenerate Fermi gases of magnetic atoms [42]. In the near future, intriguing dipolar many-body phenomena such as modifications of collective excitation modes [43], distortion [42] or the collapse [44] of the Fermi sea should be observable in suitable trap geometries and with improved detection of the cloud expansion.…”
Section: Discussionmentioning
confidence: 79%
“…In the opposite case of a relatively small-radius confinement potential, the hydrodynamic approach used in Reference [20] can effectively determine spectra of discrete low-lying modes. Another promising development of the present study is related to the collective modes in ultra-cold Fermi gases with dipolar interactions intensely investigated recently [30][31][32]. Different interaction potentials, as well as a deformation of the Fermi surface [32] can be straightforwardly incorporated in the GPF approach.…”
Section: Discussionmentioning
confidence: 99%
“…Another promising development of the present study is related to the collective modes in ultra-cold Fermi gases with dipolar interactions intensely investigated recently [30][31][32]. Different interaction potentials, as well as a deformation of the Fermi surface [32] can be straightforwardly incorporated in the GPF approach. Finally, we note that the path-integral technique used here has as a specific advantage over some other methods that it explicitly allows the studying of damped collective modes at non-zero temperatures, relevant to the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [47,48,55] more recently investigated the effect of the dipolar anisotropy on the time-of-flight expansion and on the angular dependence of the Fermi surface deformation of the ground state in relation to the trap anisotropy, and found that the Fermi surface deforms maximally when the dipoles are tilted along the less confined trap direction. Here, we analyze the interplay of this effect with the otherwise predominant shell structure in the weakly interacting regime.…”
Section: Introductionmentioning
confidence: 99%